DECADE OF IT STRATEGIC PLANNING: SYSTEMATIC REVIEW OF FRAMEWORKS AND CRITICAL SUCCESS FACTORS - Bambang Suhartono; Tole Sutikno; Imam Riadi (LPPM Nusa Mandiri, 2026)
Strategic planning for information technology (PSTI) is a crucial element in ensuring alignment between an organisation's business objectives and the use of information technology. In the last decade, challenges have arisen in adopting appropriate frameworks, methods and principles, especially amidst the complexities of digital disruption. This study aims to conduct a systematic literature review (SLR) of PSTI-related research during the period 2015-2024 using the PRISMA 2020 approach, with literature searches from leading academic databases such as Scopus, IEEE Xplore, SpringerLink, and Google Scholar during the period 2015-2024. A total of 62 scientific articles were analysed to evaluate the frameworks used, business sectors based on KBLI, implementation methods, principles applied, and critical success factors and research gaps. The results showed that Ward & Peppard, TOGAF, and Tozer frameworks were the most dominant approach. Key success factors include top management support, business and IT strategy alignment, effective IT governance, and organisational capability. This study makes a significant contribution to the development of theoretical foundations and practical guidelines for adaptive PSTI implementation, the KBLI-PSTI mapping, the systensis of framework/ methods/ princiles, alignment factors & organizational capabilities, and opens space for further research in less explored sectors